Declarations for the construction of new conventional railway lines in the years 1990 - 2020 - Janusz Engelhardt (Przegląd Komunikacyjny)
Abstract: The subject of the article are the plans to build conventional railway lines in Poland over the three decades 1990 - 2020. The first part contains a brief overview of the development stages of the Polish railway network after World War II. On the other hand, in the second part, the declarations or intentions to build new conventional lines reported in government documents in the years 1990-2020 were analyzed. In this part, the project of building a new line Podłęże - Szczyrzyc - Tymbark, along with the modernization of the existing Chabówka - Nowy Sącz line, is discussed in more detail. The further part of the article indicates that a radical breakthrough in declaring the need to build new conventional railway lines took place in 2017 and in the following years, when a completely new concept for the construction of the Central Communication Port (CPK) in Baranów near Warsaw was published and preparations for this construction began. The total length of new, conventional sections of railway lines to be built as part of the STH construction project by 2035 is over 900 km. These sections have been specified with the emphasis on the fact that in the following years in-depth analyzes as to the legitimacy of their construction are necessary. Keywords: Transport policy; Railway infrastructure; Linear investments